A nearly intact bombarde in the western Black Sea: initial observations - Garbov , Dragomir (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
This paper discusses a shipwreck recorded by the Black Sea Maritime Archaeology Project. The site lies in 137 m of water on Bulgaria’s continental shelf. It represents the remains of a 20-metre-long two-masted wooden sailing ship. Physical evidence was examined against documentary sources in an attempt to contextualise the archaeological site. The vessel is discussed as an early 19th century bombarde, a light cruiser or armed merchantman typical for the region of Provence, but also built in other parts of the Mediterranean. The shipwreck symbolises the re-integration of the Black Sea in the globalised maritime world of the ‘long nineteenth century.’